Does the ranking position predict the final combat outcome in senior and junior judo athletes? - Courel-Ibanez, J.; Escobar-Molina, R.; Franchini, E. (Revista de Artes Marciales Asiaticas, 2018)
The aim of this study was to identify whether ranking position predicts combat result in Senior and Junior male and female Spanish judo athletes, and how it influences the different stages of the championship. The sample was composed of 683 combats from the Senior (male = 164; female = 158 combats) and Junior (male = 193; female = 168 combats) Spain 2014 Judo National Championships, including all weight categories. Data were obtained from the official classification published by the Spanish Judo Federation. Main results revealed important advantages of high-ranked athletes, finding differences between sexes and championship stages. Specifically, high-ranked athletes had more probability of winning and passing to the next stage. This advantage appears to be greater at the initial phases in females but mitigated as the championship progresses. Interestingly, the quarterfinal appears to be a critical phase in which better skilled and prepared athletes are likely to win. Greater differences between better and lower-ranked were found in Junior females, especially at eliminatory and quarterfinals stages. On the contrary, the Junior male contest appears to be the most equitable competition. These results fuel the debate about the seeding process in judo championships.